Análise praxeológica dos Passeios Aleatórios da Mônica - Nagamine, Camila MacEdo Lima; Henriques, Afonso; Utsumi, Miriam Cardoso [UNESP]; Cazorla, Irene Mauricio (My University, 2011)
This paper aims to present the possible contributions of Anthropological Theory of Didactics in a priori analysis of the didactic sequence The Random Walks of Monica. This sequence addresses elementary concepts of probability theory for Basic Education, and has undergone improvements based on the recommendations of the National Curricular Parameters, favoring active participation of the subjects, who constantly interact with the tasks and are challenged to make decisions regarding each result. Analysis revealed that this sequence makes it possible to highlight a complete praxeological organization (Task/Technique/Technology/Theory) and reverses the usual praxeology, because it starts with a problem situation, from which emerge the intuitive conceptions of probabilit, the frequentist probability, resulting from random experimentation, and the theoretical probability (Laplace) calculated from the mathematical modeling, using the diagram of possibilities.
Praxeological analysis of the Random Walks of Monica
Keywords: Anthropological theory of didactics; Basic education; Didactic sequence; National curricular parameters; Teaching of probability